MANAJEMEN DAKWAH DALAM MENINGKATKAN PERILAKU BERIBADAH SANTRI PONDOK PESANTREN DARUN NAJAH PETAHUNAN KECAMATAN SUMBERSUKO LUMAJANG - Moh. Muafi Bin Thohir (Dakwatuna: Jurnal Dakwah dan Komunikasi Islam, 2020)
Behavior of santri worship at Darun Najah Islamic Boarding School PetahunanSumbersuko Lumajang, which lacks religious behavior such as a number of santri who stilldo not pray on time like dawn prayers, do not follow the activities of routine dhikr, do notread the Koran according to the specified schedule and other worship activities, areseparate problems for da'wah which need to be managed systematically through Da'wahmanagement so that they have good worship behavior. This study uses a qualitativemethod with the case study approach. The results of the study show that 1) Theimplementation of preaching management in the Islamic boarding school of Darun NajahPetahunan, Sumbersuko Subdistrict, Lumajang in improving santri worship behavior, iscarried out by planning, organizing, actualizing and overseeing the preaching program ofsantri worship behavior through the study of the yellow book material, the pesantrenculture developed is both mahdla and and ghairu mahdha. By upholding the culture ofta'dzim and polite behavior towards others and seniority created worship behavior on thestudents who not only know the teachings of Islam but also carry out the teachings ofIslam with their own awareness. 2) Supporting factors for the management of Islamicboarding school Darun Najah Petahunan Sumbersuko District Lumajang in improving thebehavior of students of religious worship include factors that desire students who havehimmah (enthusiasm) for learning, the participation of parents, awareness of runningworship services and reciting the mosque, the location of the mosque in front of theboarding school and the caregivers and religious teachers who always provide role modelsand have a good society. While the inhibiting factors are lack of discipline, the effect ofinformation technology development, increasingly negative association, theinconvenience of students to regulations, so that they require the involvement ofstudents, more affirmation of caregivers and better management of funding, increasedintensity of meetings and performance of administrators and caregivers who are closer tostudents to overcome the negative effects of information technology.